Response of Blood Pressure to Renal Denervation Is Not Associated with Genetic Variants - Delles, Christian; Schmieder, Roland; Daly, Rónán; Kannenkeril, Dennis; Bosch, Agnes; Lauder, Lucas; Kunz, Michael; Böhm, Michael; Hamilton, Graham; Schmieder, Raphael; Schmid, Axel; Herzyk, Pawel; et al. (Hypertension, 2024)
BACKGROUND: Renal denervation lowers blood pressure (BP) in patients with uncontrolled hypertension. We conducted an unbiased genomic screen to identify genetic variants that may associate with BP response to renal denervation (RDN). METHODS: Patients (n=268) with uncontrolled resistant hypertension (baseline BP, 166±21/90±15 mm Hg) who underwent endovascular RDN using the Symplicity catheter (Medtronic, Inc, Santa Rosa, CA) were included. Reduction in 24-hour ambulatory systolic BP was assessed at 6 months and divided into 2 groups: above and below the median response of 6.0 mm Hg, taking preintervention 24-hour ambulatory BP and regression to the mean into account. Whole exome sequencing assessing 249 669 variants, was conducted using Illumina NovaSeq technology read on a NovaSeq S4 Flow Cell device. RESULTS: We did not identify individual gene variants associated with BP response following RDN. These findings were confirmed after adjustment for sex and in a sensitivity analysis looking at tertiles of BP response. We also explored specific variants in AGT, ADD1, ADRB1, ADRB2, and SCNN1A that have been proposed as potential candidate genes for response and found no association (all P>0.13). Gene ontology analysis of variants across the 2 responder groups highlighted differences in biologic processes such as cell adhesion and molecular function such as protein tyrosine kinase activity. CONCLUSIONS: The response to RDN, in terms of 24-hour BP reduction, was not associated with the genetic profile of patients with resistant hypertension. These data do not support the use of a genetic score to identify potential responders to RDN.
CRIS-Team Scopus Importer:2024-12-06
Keywords: blood pressure; catheters; genetic profile; genomics; hypertension